Impact of magnetorheological fluid composition on their behaviour in gradient pinch mode - Jiří Žáček; Zbyněk Strecker; Filip Jeniš; Ondřej Macháček; Janusz Goldasz; Bogdan Sapinski; Martin Vrbka; Michal Kubík (Scientific Reports)
Abstract Magnetorheological (MR) fluids can be utilized in one of the fundamental operating modes of which the gradient pinch mode has been the least explored. In this unique mode non-uniform magnetic field distributions are taken advantage of to develop a so-called Venturi-like contraction in MR fluids. By adequately directing magnetic flux the material can be made solidified in the regions near the flow channel wall, thus creating a passage in the middle of the channel for the fluid to pass through. This leads to unique variations of the slope in the pressure-flow rate characteristics. It can be stated that the effect of the MR fluid composition on the behaviour of the MR fluid in gradient pinch mode has not been thoroughly investigated yet. In this study, the behaviour of MR fluids was assessed with a dedicated pinch mode MR valve that provided a valuable insight into the contraction mechanism using fluorescence microscopy. Briefly, seven MR fluid samples were prepared with different particle concentrations (10%, 22% and 32 vol%) and mean particle sizes (2, 4.5 and 8.2 μm). It was found that the MR fluid sample with the larger particle size exhibits a significantly larger slope change observed in the pressure-flow rate characteristics. Increasing the particle size from 2 μm (base) to 8 μm resulted in the slope increase by a factor of 2.6 compared to the base sample. Increasing the particle concentration has a negligible effect on the pinch mode effect. Finally, these results were analysed using the modified Wuest equation, which is commonly used for characterizing sharp-edged orifices in low Reynolds number flow regimes. The simple equation was determined to describe the behaviour of MR fluids in gradient pinch mode with adequate accuracy.